2013
DOI: 10.1371/journal.pone.0071591
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Variation between Colour Patterns in a Temperate Protogynous Hermaphrodite, the Ballan Wrasse Labrus bergylta

Abstract: Fish populations are often treated as homogeneous units in typical fishery management, thereby tacitly ignoring potential intraspecific variation which can lead to imprecise management rules. However, intraspecific variation in life-history traits is widespread and related to a variety of factors. We investigated the comparative age-based demography of the two main colour patterns of Labrus bergylta (plain and spotted, which coexist in sympatry), a commercially valuable resource in the NE Atlantic. Individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 51 publications
2
20
0
7
Order By: Relevance
“…A previous study on spotty and plain morphotypes of ballan wrasse reported differences in growth trajectories, size at age, otolith length to body length, and mortality (Villegas-Ríos et al 2013b), and also in investment in reproduction versus growth (Villegas-Ríos 2013). Based upon those results, which included extensive growth and maturation analyses, it was concluded that there was likely to exist large genetic differences between these 2 morphotypes.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A previous study on spotty and plain morphotypes of ballan wrasse reported differences in growth trajectories, size at age, otolith length to body length, and mortality (Villegas-Ríos et al 2013b), and also in investment in reproduction versus growth (Villegas-Ríos 2013). Based upon those results, which included extensive growth and maturation analyses, it was concluded that there was likely to exist large genetic differences between these 2 morphotypes.…”
Section: Discussionmentioning
confidence: 96%
“…one is primarily spotty and the other primarily plain). If this is the case, then some of the observed differences in traits between the spotty and plain morphotypes as reported by Villegas-Ríos et al (2013b) may actually represent underestimates of the differences between the 2 genetic groups as there is no exact coincidence between morphotype and genetic grouping. Further studies using larger numbers of individuals and markers, and matching extensive life-history and trait data to the genetic data will be required to fully resolve this issue.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In general, most of the species were correctly identified, but in some cases, different species were pooled under the same morphotype designation; for example, annular sea bream Diplodus annularis (L.), white sea bream D. sargus (L.) and common two-banded sea bream D. vulgaris (Geoffroy Saint-Hilaire) were identified under the morphotype white sea bream, while in other cases the same species were identified as different morphotypes designation, for example ballan wrasse Labrus bergylta (Ascanius) was identified as two different morphotypes 'pintos' and 'maragotas' (see Villegas-R ıos et al 2013). The term species was used to refer to morphotype (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…It inhabits rocky reefs and kelp beds at depths up to 60 m depth where it mostly feeds on small invertebrates (Figueiredo et al ., ). It's a long‐lived wrasse (≤ 30 years) with slow growth, although demographic parameters vary between the two main morphotypes that have been described: plain and spotted (Villegas‐Ríos et al ., ). As a protogynous hermaphrodite, all individuals are born females with sex change being very plastic (it occurs on average at 36 cm total length ( L T ) in plain morphotypes and 47.2 cm L T in spotted morphotypes).…”
Section: List Of Individual Labrus Bergylta Identified At the Same Spmentioning
confidence: 99%